2020
DOI: 10.1016/j.ajpath.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Automated Breast Cancer Detection to Identify Spatial Distributions of Tumor-Infiltrating Lymphocytes in Invasive Breast Cancer

Abstract: Quantitative assessment of Tumor-TIL spatial relationships is increasingly important in both basic science and clinical aspects of breast cancer research. We have developed and evaluated convolutional neural network (CNN) analysis pipelines to generate combined maps of cancer regions and tumor infiltrating lymphocytes (TILs) in routine diagnostic breast cancer whole slide tissue images (WSIs). We produce interactive whole slide maps that provide 1) insight about the structural patterns and spatial distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…An added advantage of computational methods is the potential to additionally address the spatial distribution of TILs and thus provide insights into the biologic and clinical significance of distribution patterns and TILs-tumour interactions. The significance of spatial distribution and hot spots has recently been examined in BC using artificial intelligence algorithms [27][28][29] and data suggest that spatial distribution may provide added prognostic information [27].…”
Section: Discussionmentioning
confidence: 99%
“…An added advantage of computational methods is the potential to additionally address the spatial distribution of TILs and thus provide insights into the biologic and clinical significance of distribution patterns and TILs-tumour interactions. The significance of spatial distribution and hot spots has recently been examined in BC using artificial intelligence algorithms [27][28][29] and data suggest that spatial distribution may provide added prognostic information [27].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the ResNet34 was the best performer in both cancer detection task and lymphocyte detection task, even surpassing the Saltz study's accuracy in the case of breast cancer. Using their ResNet34 model, Le et al (2020) showed that their estimated TIL infiltration was a significant survival predictor.…”
Section: Region Of Interest-level Analysis Methodsmentioning
confidence: 99%
“…Most studies of computational TILs have employed patch- or object detection-based approaches [ 26 , 27 , 28 , 29 ] with manual region outlining as part of the pipeline [ 30 ]. Some of these also used multiplexed immunofluorescence (mIF) [ 31 ] or immunohistochemistry (IHC) [ 32 , 33 ] to classify cells as lymphocytes.…”
Section: Introductionmentioning
confidence: 99%